Self-selected vs. prescribed aerobic exercise intensity: impacts on pleasure in women with obesity - Carlos Eduardo Rosa Da Silva; Wilian Jesus Santana; Gustavo Almeida; Adriano Verame; Antonio Roberto Doro; Eduardo Barbosa; Leonardo Lima; Helton Magalhães Dias; Marcelo Callegari Zanetti; Aylton Figueira Junior (Frontiers in Psychology)
IntroductionSelf-selection of aerobic training intensity is an approach that allows practitioners to develop autonomy (choice of pace), improve physical fitness, and contribute to better affective responses and training adherence. However, it is still unclear whether self-selection of training intensity in group settings is comparable to individual training conditions. The aim of the present study was to compare the effect of three aerobic training protocols on psychophysiological responses in physically inactive adult obese women.MethodsThe sample consisted of 90 women with a mean age of 48.3 ± 5.5 years and BMI of 31.2 ± 4.8 kg/m2, who participated in three treadmill aerobic training protocols: 1- Control group (IPI) with individually prescribed intensity (64 to 76% of HRmax), 2- Small group (SGS) with self-selected intensity, and 3- Individual with self-selected intensity (ISS). Heart rate (HR), total session volume (VL), affective valence was determined by feeling scale (FS), enjoyment was determined by Physical Activity Enjoyment Scale (PACES), intention to repeat the exercise session (INT), and Basic Psychological Needs Satisfaction Scale (BPNFS) were evaluated. Statistical analyses were conducted using two-way ANOVA for HR and FS, and one-way ANOVA for VL, PACES, INT, and BPNFS with Tukey post hoc test and significance criteria (p < 0.05).ResultsThe results showed that HR and VL were similar (p > 0.05) between the protocols IPI, SGS and ISS, while FS, PACES, and INT were significantly higher in SGS and ISS than IPI protocols (p < 0.05). BPNFS also presented better results for the SGS and ISS protocols (p < 0.05).DiscussionThese findings suggest that the intensity and training volume were similar among different protocols. Affective responses were more positive perceived in SGS and ISS protocols.ConclusionWe conclude that intensity self-selection is a safe, effective, and comparable strategy to prescribed intensity at moderate levels, providing a more enjoyable experience that may contribute to greater adherence to aerobic training.